2018
DOI: 10.14419/ijet.v7i2.4.10042
|View full text |Cite
|
Sign up to set email alerts
|

Development of smart farming - a detailed study

Abstract: Agriculture is the backbone of every country. The country's development is not due to Industrial development alone, but also due to the agriculture development. The Country like India depends upon the 70 percent of the agriculture. In the recent year's agriculture productions got down due to the natural disasters like flood, famine and etc., hence the country should implement the latest technology to overcome the problems in agriculture. Recently Internet of Things (IoT) is the latest technology used in all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Smart agriculture uses Information Technology (ICT) and specifically, the Internet of Things (IoT) and associated extensive analytic data to overcome these challenges through electronic crop tracking, as well as the environment, soil, fertilization, and planting conditions [11]. The intelligent farming system that is a system that can control; temperature sensor, soil moisture sensor, air humidity sensor and another sensor at the sensor node and The Wireless sensor network (WSN) consists of a large number of sensor nodes can collect data and are sent to the base station [12]. Smart agriculture relies on data transmission and data concentration from many sensors in remote receiving systems to allow the combination and analysis of various agricultural data that can be used as a basis for making decisions to control agricultural land [2].…”
Section: Introductionmentioning
confidence: 99%
“…Smart agriculture uses Information Technology (ICT) and specifically, the Internet of Things (IoT) and associated extensive analytic data to overcome these challenges through electronic crop tracking, as well as the environment, soil, fertilization, and planting conditions [11]. The intelligent farming system that is a system that can control; temperature sensor, soil moisture sensor, air humidity sensor and another sensor at the sensor node and The Wireless sensor network (WSN) consists of a large number of sensor nodes can collect data and are sent to the base station [12]. Smart agriculture relies on data transmission and data concentration from many sensors in remote receiving systems to allow the combination and analysis of various agricultural data that can be used as a basis for making decisions to control agricultural land [2].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and controlling the environment with the help of IoT is part of smart farming [7]. It involves censorship and internet connection to collect a variety of data parameters such as humidity, temperature, motion, health, position, etc., and keep it on track with the farmers [8]. The study of monitoring and control systems is commonly found for poultry for hatching the eggs and keep the quality of the meat [9]- [12], for monitoring the environment and health of cattle [13], controlling the climate change adaptation for cattle and goats [14].…”
mentioning
confidence: 99%